Lactation and cardiovascular risk factors in mothers in a population-based study: the HUNT-study - Natland Siv T; Nilsen Tom I L; Midthjell Kristian; Andersen Lene F; Forsmo Siri (BMC, 2012)
Abstract Background Lactation has beneficial short term effects on maternal metabolic health, but the long term effects are less well known. Methods We studied the association between lifetime duration of lactation and cardiovascular risk factors in mothers later in life among 21,368 parous women aged 20 to 85 years attending the second Nord-Trøndelag Health Study (HUNT2) in 1995-1997, Norway, a cross-sectional population-based study. General linear modelling was used to calculate mean values of known cardiovascular risk factor levels in five categories of lifetime duration of lactation. Logistic regression was conducted to estimate odds ratios of hypertension, obesity and diabetes. Results Among women aged 50 years or younger, lifetime duration of lactation was significantly and inversely associated with body mass index (P-trend, < 0.001), waist circumference (P-trend, < 0.001), systolic and diastolic blood pressure (both P-trends, < 0.001), and serum levels of triglycerides, total cholesterol and low density lipoprotein cholesterol (all P-trends, < 0.001) after adjustment for covariates. Parous women aged 50 years or younger who had never lactated had higher prevalence of hypertension, obesity and diabetes. In this age group, compared to women who had lactated for 24 months or more, parous women who had never lactated had an OR for hypertension of 1.88 (95% CI 1.41, 2.51), an OR for obesity of 3.37 (95% CI 2.51, 4.51) and an OR for diabetes of 5.87 (95% CI 2.25, 15.3). Among women older than 50 years there were no clear associations. Conclusion Lifetime duration of lactation was associated with long term reduced cardiovascular risk levels in mothers aged 50 years or younger.